Minimizing tourist impact on the Argentine Islands ecosystem, Antarctic Peninsula, using visitor site guidelines approach - H. Yevchun; E. Dykyi; I. Kozeretska; A. Fedchuk; V. Karamushka; I. Parnikoza (Ukrainian Antarctic Journal, 2021)
There has been an ongoing increase in tourist visits to the Antarctic since 2010. These visits primarily concentrate on a small number of sites, increasing the possible environmental impact. One of the tourism hotspots is the central Argentine Islands in Wilhelm Archipelago. These islands, being one of the top 20 most visited Antarctic sites, consist of Galindez Island, Winter Island, and Skua Island. They are known for wildlife, rich vegetation (old moss banks, rich bryophyte and lichen communities, Antarctic pearlwort Colobanthus quitensis and hairgrass Deschampsia antarctica populations), spectacular views. They include one of the oldest Antarctic research stations: the Ukrainian Antarctic Akademik Vernadsky station. Previously no measures have been developed to minimize the impact of tourism on this region. Thus, the Visitor Site Guidelines (VSG) approach and the numerous studies in the region were used to determine the central values of this site and to identify those key features that can be opened for tourists. In addition to the most frequently mentioned values, such as seabirds and mammals, we considered it necessary to mention the vegetation. We assessed threats to these values, distinguishing known and potential impacts. We have also analyzed and developed landing requirements for the studied area, including the most critical requirement to be considered, namely the number of visitors. We think that the maximum number of visitors should be 36 at any time and 270 per day, not counting passengers of yachts. This is the first time that the Visitor Site Guidelines were modified to limit the number of yachts visiting the site to three yachts per day. To reduce the tourist load at the station itself and at the same time to concentrate tourists in the studied region, we proposed two tourist trails: one for Galindez Island, the other — the existing trail for Winter Island. The prepared draft of Visitor Site Guidelines is given in Appendix 2.